The burden of disease in Greece, health loss, risk factors, and health financing, 2000–16: an analysis of the Global Burden of Disease Study 2016. (August 2018) - ,; Tyrovolas, Stefanos; Kassebaum, Nick J; Stergachis, Andy; Abraha, Haftom N; Alla, François; Androudi, Sofia; Car, Mate; Chrepa, Vanessa; Fullman, Nancy; Fürst, Thomas; Haro, Josep Maria; et al.
Summary: Background: Following the economic crisis in Greece in 2010, the country's ongoing austerity measures include a substantial contraction of health-care expenditure, with reports of subsequent negative health consequences. A comprehensive evaluation of mortality and morbidity is required to understand the current challenges of public health in Greece. Methods: We used the results of the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2016 to describe the patterns of death and disability among those living in Greece from 2000 to 2010 (pre-austerity) and 2010 to 2016 (post-austerity), and compared trends in health outcomes and health expenditure to those in Cyprus and western Europe. We estimated all-cause mortality from vital registration data, and we calculated cause-specific deaths and years of life lost. Age-standardised mortality rates were compared using the annualised rate of change (ARC). Mortality risk factors were assessed using a comparative risk assessment framework for 84 risk factors and clusters to calculative summary exposure values and population attributable fraction statistics. We assessed the association between trends in total, government, out-of-pocket, and prepaid public health expenditure and all-cause mortality with a segmented correlation analysis. Findings: All-age mortality in Greece increased from 944·5 (95% uncertainty interval [UI] 923·1–964·5) deaths per 100 000 in 2000 to 997·8 (975·4–1018) in 2010 and 1174·9 (1107·4–1243·2) in 2016, with a higher ARC after 2010 and the introduction of austerity (2·72% [1·65 to 3·74] for 2010–16) than before (0·55% [0·24 to 0·85] for 2000–10) or in western Europe during the same period (0·86% [0·54 to 1·17]). Age-standardised reduction in ARC approximately halved from 2000–10 (−1·61 [95% UI −1·91 to −1·30]) to 2010–16 (−0·87% [–2·03 to 0·20]), with post-2010 ARC similar to that in Cyprus (−0·86% [–1·4 to −0·36]) and lower than in western Europe (−1·14% [–1·48 to −0·81]). Mortality changes in Greece coincided with a rapid decrease in government health expenditure, but also with aggregate population ageing from 2010 to 2016 that was faster than observed in Cyprus. Causes of death that increased were largely those that are responsive to health care. Comparable temporal and age patterns were noted for non-fatal health outcomes, with a somewhat faster rise in years lived with disability since 2010 in Greece compared with Cyprus and western Europe. Risk factor exposures, especially high body-mass index, smoking, and alcohol use, explained much of the mortality increase in Greek adults aged 15–49 years, but only explained a minority of that in adults older than 70 years. Interpretation: The findings of increases in total deaths and accelerated population ageing call for specific focus from health policy makers to ensure the health-care system is equipped to meet the needs of the people in Greece. Funding: Bill & Melinda Gates Foundation.